Incidence of Malaria in HIV-infected and uninfected and Rwandan women from 2005 to 2011 - Umunyana, Jacqueline (My University, 2014)
Malaria in HIV-infected (HIV+) persons is associated with reduced immunity due to a decrease in CD4+ cells count and an increase in viral load, and immunity becomes more compromised in HIV-infected ART-naïve patients. However, the relationship between treatment of HIV infection with antiretroviral therapy (ART) and malaria among HIV coinfected individuals has not been widely reported in Africa, in particular amongst Rwandan women. In this study, the investigator examined malaria incidence and its associated potential risk factors in a cohort of HIV-uninfected, HIV-infected on ART and HIV-infected naïve Rwandan women. Method The data used in this research consists of 936 women enrolled in the Rwandan Women's Inter-association Study and Assessment (RWISA) study. Follow-up visits were carried out every 6 months for a period of 5 years. Incidence of malaria was considered as self-reported if it occurred during the 6 months prior to the study visit. Incidence rates (IRs) and Hazard ratios (HRs) with 95% CI were determined in HIV-uninfected, HIV-infected ART-naïve and HIV-infected on ART groups. Predictors of malaria incidence in these groups were estimated by Hazard ratios (HR, 95% CI) using Cox regression adjusted for potential confounders. Results Of the 936 women enrolled in the study (226 HIV-uninfected and 710 HIV-infected), almost 90% of the women reported malaria during the follow-up period. At the baseline visit, the median age of the participants was lower among HIV-infected women at 34 years ([IQR] 30- 39), compared to that of HIV-uninfected women at 43 years ([IQR] 34-49), P<0.01. In both groups of HIV-infected and HIV-uninfected women, a large number were widowed i.e. 49% vs. 42%, P<0.01 The HIV-infected women had lower educational status (67% vs. 57%, P<0.01) and lower employment opportunities (68% vs 72%, P=0.002) than HIV-uninfected women. Of the HIVuninfected women, 174 (77%) and of HIV-infected women 596 (84%) reported that they did not have enough food to eat. Malaria incidence was higher in HIV-infected ART-naïve women [adjusted HR= 1.2, 95% CI (1.01-1.36), P=0.03], when compared to HIV-infected women on ART. However, when malaria incidence was compared according to HIV status, HIV-infected women showed a significantly lower incidence when compared to their HIV-uninfected counterparts [adjusted HR= 0.8, 95% CI (0.69- 0.97), P=0.02]. The independent predictors of malaria incidence in the cohort were unemployment, lower level of education, age and season. Conclusion HIV-infected antiretroviral-naïve women in malaria-endemic areas are at higher risk of malaria than HIV-infected women on antiretroviral therapy. In countries where both diseases overlap, the indirect effect of HIV treatment with combination antiretroviral therapy could reduce malaria burden. These findings suggest that additional malaria prevention efforts should be aimed at the untreated HIV-infected population.
A research report submitted to the School of Public Health , University of Witwatersrand Johannesburg in partial fulfillment of the requirements for the degree of Masters of Science in Epidemiology and Biostatistics, November 2013
Keywords: Malaria--Rwanda; HIV--Rwanda